SOS1, HKT1;5, and NHX1 Synergistically Modulate Na+ Homeostasis in the Halophytic Grass Puccinellia tenuiflora - Zhang, Wei-Dan; Wang, Pei; Bao, Zhulatai; Ma, Qing; Duan, Li-Jie; Bao, Ai-Ke; Zhang, Jin-Lin; Wang, Suo-Min (Frontiers in Plant Science, 2017)
Puccinellia tenuiflora is a typical salt-excluding halophytic grass with excellent salt tolerance. Plasma membrane Na+/H+ transporter SOS1, HKT-type protein and tonoplast Na+/H+ antiporter NHX1 are key Na+ transporters involved in plant salt tolerance. Based on our previous research, we had proposed a function model for these transporters in Na+ homeostasis according to the expression of PtSOS1 and Na+, K+ levels in P. tenuiflora responding to salt stress. Here, we analyzed the expression patterns of PtSOS1, PtHKT1;5 and PtNHX1 in P. tenuiflora under 25 and 150 mM NaCl to further validate this model by combining previous physiological characteristics. Results showed that the expressions of PtSOS1 and PtHKT1;5 in roots were significantly induced and peaked at 6 h under both 25 and 150 mM NaCl. Compared to the control, the expression of PtSOS1 significantly increased by 5.8 folds, while that of PtHKT1;5 increased only by 1.2 folds in roots under 25 mM NaCl; on the contrary, the expression of PtSOS1 increased by 1.4 folds, whereas that of PtHKT1;5 increased by 2.2 folds in roots under 150 mM NaCl. In addition, PtNHX1 was induced instantaneously under 25 mM NaCl, while its expression was much higher and more persistent under in shoots 150 mM NaCl. These results provide stronger evidences for the previous hypothesis and extend the model which highlights that SOS1, HKT1;5 and NHX1 synergistically regulate Na+ homeostasis by controlling Na+ transport systems at the whole-plant level under both lower and higher salt conditions. Under mild salinity, PtNHX1 in shoots compartmentalized Na+ into vacuole slowly, and vacuole potential capacity for sequestering Na+ would enhance Na+ loading into the xylem of roots by PtSOS1 through feedback regulation; and consequently, Na+ could be transported from roots to shoots by transpiration stream for osmotic adjustment. While under severe salinity, Na+ was rapidly sequestrated into vacuoles of mesophyll cells by PtNHX1 and the vacuole capacity became saturated for sequestering more Na+, which in turn regulated long-distance Na+ transport from roots to shoots. As a result, the expression of PtHKT1;5 was strongly induced so that the excessive Na+ was unloaded from xylem into xylem parenchyma cells by PtHKT1;5.